1989
DOI: 10.1093/geront/29.4.449
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Depression in Family Caregivers

Abstract: Family caregivers who sought help to increase their coping skills (N = 158) and caregivers who volunteered for a longitudinal study of Alzheimer's disease (N = 58) were screened for depression. Among help-seekers, 46% had depression according to Research Diagnostic Criteria (RDC), but among non-help-seekers, only 18% met this criterion. In general, women were more depressed than men, but no major differences in the extent of depression were found in those who cared for more impaired persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
148
4
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 286 publications
(159 citation statements)
references
References 0 publications
3
148
4
4
Order By: Relevance
“…Caregiving for a loved one with dementia, neurological illness, and other chronic disabling medical illness is known to be very stressful. Depression rates are high in this setting [5]- [8], and there are serious consequences for caregiver physical health as well [9]- [11]. For many of individuals, religious beliefs and practices give meaning to the caregiving role and surround the person with a supportive community that helps give strength to continue in that difficult and often isolating role.…”
Section: Introductionmentioning
confidence: 99%
“…Caregiving for a loved one with dementia, neurological illness, and other chronic disabling medical illness is known to be very stressful. Depression rates are high in this setting [5]- [8], and there are serious consequences for caregiver physical health as well [9]- [11]. For many of individuals, religious beliefs and practices give meaning to the caregiving role and surround the person with a supportive community that helps give strength to continue in that difficult and often isolating role.…”
Section: Introductionmentioning
confidence: 99%
“…Markers of depression include drug use, family strain, institutionalization of the care recipient, and discontinuation of care (Arai, Suguira, Washio, & Kudo, 2001;Gallagher et al, 1989). However, information concerning caregiver depression has been primarily limited to studies where samples included family members caring for dementia patients, spousal caregivers, and a small percentage of caregivers below 35 years of age (Whitlatch, Feinberg, & Sebesta, 1997;Zunzunegui, LlacerCentro, & Beland, 2002).…”
Section: Depressionmentioning
confidence: 99%
“…Steffen et al (1998) found that 30% of caregivers who suffered from chronic stress also suffered depression. Gallagher et al (1989) found that on average 36% of all caregivers suffered from depression. Because the levels of depression in young adult care providers was relatively unknown, one of the important findings of the current study was that 34.1% (n = 58) of the young adult caregivers surveyed scored 16 or higher on the CES-D, indicating possible clinical depression, and 22.2% (n = 36) scored 20 or above, indicating probable clinical depression.…”
Section: Depressionmentioning
confidence: 99%
“…Geriatric depression represents a unique opportunity for the conduct of prospective studies of specified depression subtypes and possibly for characterizing patients before the onset of depression. For example, vulnerability factors that may place euthymic individuals at high risk include loss of spouse (Vinkers et al, 2004), caregiver burden (Gallagher et al, 1989;Schulz et al, 1995), medical comorbidity (Cole and Dendukuri, 2003), cancer (Illman et al, 2005), and stroke (Antai-Otong, 2004). Another example is interferoninduced depression, in which many euthymic patients develop psychiatric symptoms including depression following the initiation of treatment (Valentine et al, 1998;Musselman et al, 2001).…”
Section: Commentmentioning
confidence: 99%